Self-justification and its uses for Marcel Proust's A la recherche du temps perdu - Wassenaar, I (1997)
This study investigates the different manifestations of self-justification in A la recherche du temps perdu. Proust's novel is, famously, at once fictional and autobiographical. Written in the first person, it proposes a retrospective and confessional narrative mode as its working medium, in the manner of Saint Augustine's or Rousseau's Confessions. It is a novel fascinated by how judgement takes place. Using the 1987-89 Pléiade edition of the text, Brunet's concordance, Le Vocabulaire de Proust, and the electronic concordancing capacities of FRANTEXT (both based on the previous 1954 Pléiade edition), this study is based on close textual reading, paying particular attention to under-examined sections of A la recherche. It discovers a phenomenology of Proustian self-justification. The thesis divides into three parts. Part One focuses on the narrator's relation to an external world perceived as hostile. Chapter I shows self-justification as assimilation: attempts by the narrator to fit into aristocratic Faubourg Saint-Germain society. Part Two concentrates on rhetoric, metaphor and characterization. Chapter II argues that the rhetorical trope of digression offers elastic possibilities for self-justificatory evasiveness, defeated by narrative progression. Chapter III argues that the figure of the cloison, or permeable partition, marks moments of self-justificatory dependence on dwindling protective props, used to fend off unwanted knowledge. Chapter IV shows that self-justification as discrimination informs Proustian characterization. Part Three (Chapter V) assesses the limits of self-justification. It reads the opening of Albertine disparue, and argues that mourning is a process justifying loss to the self. In conclusion, I argue that, while self-justification as a mode of interaction with the world produces finely-tuned responses, it may also produce untrustworthy moral choices. Moral and psychological experimentation in self-justification is a vital component of Proust's narrative engine.